Chromatographic analysis of ketamine and norketamine in human plasma and urine samples - Portilla, Ma. Cristina B. (Transactions of the National Academy of Science and Technology, 2011)
In recent years, the illegal use of ketamine in the Philippines has risen and this drug is now included in the list of dangerous drugs under the Comprehensive Dangerous Drug Act of 2002. Ketamine is a fast acting anesthetic that is mostly administered by veterinarians as an animal sedative. It is also used by anesthesiologists for pediatric and elderly patients as surgical anesthesia. Complications from the use of ketamine include hallucinations and confused states which contributed to the abuse of this drug. Chromatographic analysis of ketamine and norketamine, its metabolite, was carried out using high performance liquid chromatography (HPLC) with UV detectionat 210 nm on a C18 column. The mobile phase used was 30% acetonitrile and 70% phosphate buffer (0.03M, pH 7.2). Flow rate was 0.5 ml/min and oven temperature was set at 37ᵒC. the retention time of ketamine and norketamine were found to be at at ~5.6 mins and ~11.3 mins respectively. Reproducible results were obtained with CV (%) of 7.33% or less. Linear response was obtained over a concentration range of 25 to 500 ppb. LOD for ketamine is 3.6 ppb while LOQ is 4.04 ppb. While for norketamine, LOD and LOQ values were 6.10 and 6.72 ppb respectively. Ketamine and norketamine standards were spiked in blank urine samples or human plasma sample from volunteers with no ketamine use. Linear response was also obtained over the concentration range of 25 to 500 ppb. Liquid-liquid extraction was utilized for sample preparation. Average percent recovery of ketamine spiked in blank human urine was 85.0% while in spiked human samples, it was 91.0%. This HPLC method could be utilized for routine analysis of ketamine and norketamine in human urine or plasma samples.